Integrasi Bahasa Daerah sebagai Strategi Penguatan Literasi Akademik dan Identitas Mahasiswa di Perguruan Tinggi Multibahasa - Alfrida Dabura; Agustina Afrianti Paulina Rani; Yeremias Bardi; Fensiana Pada; Viktori Viktori; Constantinus Bajo Nanggo (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2026)
This study investigates the role of local language integration as a pedagogical strategy in strengthening academic literacy and shaping students’ identities in multilingual higher education contexts. The study is grounded in the sociolinguistic reality that many students continue to use local languages in their daily lives, while academic learning predominantly relies on formal Indonesian, which is often abstract and normative. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews with lecturers and students, and document analysis. The findings reveal that local language integration functions as a cognitive, affective, and cultural bridge in academic learning. Local languages are employed as a medium for initial meaning-making, conceptual discussion, and cultural reflection before students develop ideas in academic Indonesian. This practice enhances student participation, strengthens academic literacy, and reinforces local identity within academic spaces. The study concludes that local languages are not obstacles but valuable pedagogical resources. Therefore, their integration should be systematically incorporated into higher education curricula to promote inclusive, contextual, and linguistically just learning environments.